2011
DOI: 10.1111/j.1750-3841.2011.02293.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel β‐Glucosidase from Sporidiobolus pararoseus: Characterization and Application in Winemaking

Abstract: The search for new β-glucosidase from yeast sources is important to improve the quality of wines. In this work, an S. pararoseus yeast strain has shown to be capable to produce a β-glucosidase with suitable combination of properties for functionality in wines and with potential to increase the concentration of free aroma compounds, showing good prospects for an industrial application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 24 publications
4
38
0
6
Order By: Relevance
“…The β‐glucosidase activities studied in the 4 isolates showed a pH optimum of 6.0, similar to the results obtained in Sporiobolus pararoseus (Baffi and others ). Interestingly, the β‐glucosidase activity of H. uvarum was not affected in the pH range tested.…”
Section: Discussionsupporting
confidence: 88%
“…The β‐glucosidase activities studied in the 4 isolates showed a pH optimum of 6.0, similar to the results obtained in Sporiobolus pararoseus (Baffi and others ). Interestingly, the β‐glucosidase activity of H. uvarum was not affected in the pH range tested.…”
Section: Discussionsupporting
confidence: 88%
“…The enzyme was tolerant to ethanol, showing tolerance up to 40% of ethanol (Table 2). Previous studies in literature reported cellulases and hemicellulases which are inhibited by ethanol (van DYK et al, 2010;BAFFI et al, 2011). In the present study, the enzyme remained 75% of residual activity at 40% of ethanol showing high tolerance to this compound.…”
Section: Resultssupporting
confidence: 56%
“…As β ‐glucosidases are usually inhibited by glucose, the sugar tolerance of WaExg2 is one of its outstanding features. Similar beneficial properties were reported for β ‐glucosidases produced by a few other yeast strains (Swangkeaw et al ., ; Baffi et al ., ). In addition to sugar tolerance, WaExg2 proved to be stable under various wine‐related conditions.…”
Section: Discussionmentioning
confidence: 97%